Public Opinion of Capital Punishment: An Intersectional Analysis of Race, Gender, and Class Effects. (December 2019) - Trahan, Adam; Dixon, Andrekus; Nodeland, Brooke
Extant research on the demographic correlates of capital punishment opinion has separately analyzed race, gender, and class. Intersectionality has shown a flaw of this approach is that these characteristics overlap and interact to shape people's identities and opinions. Using data from the Cumulative File of the General Social Survey (1972–2016), we regressed capital punishment opinion on respondents' race, gender, and class intersections. Findings show wide variation in opposition to capital punishment. Implications of the findings, including the superiority of the intersectional approach, are discussed.